Delegation to a Group - Sebastian Fehrler; Moritz Janas (Institute of Labor Economics (IZA), 2021)
We study the choice of a principal to either delegate a decision to a group of careerist experts, or to consult them individually and keep the decision-making power. Our model predicts a trade-off between information acquisition and information aggregation. On the one hand, the expected benefit from being informed is larger in case the experts are consulted individually. Hence, the experts either acquire the same or a larger amount of information, depending on the cost of information, than in case of delegation. On the other hand, any acquired information is better aggregated in case of delegation, where experts can deliberate secretly. To test the model's key predictions, we run an experiment. The results from the laboratory confirm the predicted trade-off, despite some deviations from theory on the individual level.
Keywords: C92; D23; D71; 330; delegation; decision rights; committees; group decision-making; expert advice; strategic communication